Online repression and tactical evasion: evidence from the 2020 Day of Anger protests in Egypt. Issue 2 (17th February 2023) - Lutscher, Philipp M.; Ketchley, Neil
ABSTRACT: Following the 2011 Arab Spring, autocrats have sought to limit citizens' ability to publicize offline protests over social media. In this article, we explore how users adjust to these restrictions. To do so, we analyse 33 million tweets sent from Egypt during the "Day of Anger" protests in September 2020. We find evidence of online tactical evasion in a highly repressive context. Compared to neutral users, regime opponents are more likely to issue calls for offline protests using new or dedicated accounts that contain no personal information. Users are also more likely to delete tweets calling for mobilization ex-post in a bid to conceal their activism. We find weaker evidence suggesting that regime opponents try to evade laws targeting critical accounts with over 5000 followers. The findings illustrate how activists in autocracies use social media to mobilize street-level contention while attempting to mitigate the risk of state repression.